NLRC4 Inflammasome-Driven Immunogenicity of a Recombinant MVA Mucosal Vaccine Encoding Flagellin - Sanos, Stephanie L.; Kassub, Ronny; Testori, Marco; Geiger, Marlene; Pätzold, Juliane; Giessel, Raphael; Knallinger, Johanna; Bathke, Barbara; Gräbnitz, Fabienne; Brinkmann, Kay; Chaplin, Paul; Suter, Mark; et al. (Frontiers in Immunology, 2018)
Bacterial flagellin enhances innate and adaptive immune responses and is considered a promising adjuvant for the development of vaccines against infectious diseases and cancer. Antigen-presenting cells (APCs) recognise flagellin with the extracellular TLR5 and the intracellular NLRC4 inflammasome-mediated pathway. The detailed cooperation of these innate pathways in the induction of the adaptive immune response following intra-nasal (i.n.) administration of a recombinant modified vaccinia virus Ankara (rMVA) vaccine encoding flagellin (rMVA-flagellin) is not known. rMVA-flagellin induced enhanced secretion of mucosal IL-1b and TNF-aresulting in elevated CTL and IgG2c antibody responses. Importantly, mucosal IgA responses were also significantly enhanced in both bronchoalveolar (BAL) and intestinal lavages accompanied by the increased migration of CD8+ T cells to the mesenteric lymph nodes (MLN). Nlrc4-/- rMVA-flagellin-immunized mice failed to elicit pulmonary CTL responses, IgG2c was lower, and IgA levels in the BAL or intestinal lavages was similar as that of control mice. Our results show the favourable adjuvant effect of rMVA-flagellin in the lung as well as the intestinal mucosa following i.n. administration with NLRC4 as the essential driver of this promising mucosal vaccine concept.